2003
DOI: 10.1046/j.1365-294x.2003.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scaled geographical population structuring in a highly mobile marine species: the Atlantic cod

Abstract: Compared with many terrestrial and freshwater environments, dispersal and interbreeding is generally much less restricted in the marine environment. We studied the tendency for a marine species, the Atlantic cod, to be sub-structured into genetically differentiated populations on a fine geographical scale. We selected a coastal area free of any obvious physical barriers and restricted sampling to a 300-km region, well within the dispersal ability of this species. Screening 10 polymorphic microsatellite loci in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
290
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(317 citation statements)
references
References 60 publications
24
290
1
2
Order By: Relevance
“…Skarstein et al 2007, Pampoulie et al 2008a. In the present study, we also found differences among discrete populations within a spawning complex (F ST = 0.0039 to 0.0061) that were consistent with fine-scale differences documented among nearby fjords (separated by 60 to 300 km) in Norway (F ST = 0.0013 to 0.0054, PanI not used, Knutsen et al 2003) and among cod in Icelandic waters (F ST = 0.0030, excluding PanI, Pampoulie et al 2006). Weak genetic differentiation may be a result of the recent origin of cod populations (Pampoulie et al 2008a).…”
Section: Spawning Stock Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…Skarstein et al 2007, Pampoulie et al 2008a. In the present study, we also found differences among discrete populations within a spawning complex (F ST = 0.0039 to 0.0061) that were consistent with fine-scale differences documented among nearby fjords (separated by 60 to 300 km) in Norway (F ST = 0.0013 to 0.0054, PanI not used, Knutsen et al 2003) and among cod in Icelandic waters (F ST = 0.0030, excluding PanI, Pampoulie et al 2006). Weak genetic differentiation may be a result of the recent origin of cod populations (Pampoulie et al 2008a).…”
Section: Spawning Stock Structuresupporting
confidence: 90%
“…Yet, recent research shows that larval recruitment for some marine organisms, including cod, may occur on a local scale. In Atlantic cod, local recruitment has been linked to fine-scale habitat associations (Bradbury et al 2008) and egg and larval retention has been hypothesized as a mechanism promoting fine-scale genetic structure (Knutsen et al 2003, Jorde et al 2007). Norwegian cod may select spawning sites within sheltered fjords to minimize advection of pelagic larvae ).…”
Section: Mechanisms Of Population Structuringmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive mtDNA analyses have found little or no structure in waters off the coasts of eastern North America (Carr, Snellen, Howse, & Wroblewski, 1995), Iceland (Árnason, Pálsson, & Arason, 1992; Árnason, Petersen, Kristinsson, Sigurgíslason, & Pálsson, 2000), the Faroe Islands (Sigurgíslason & Árnason, 2003), Norway (Árnason & Pálsson, 1996), and the Baltic Sea (Árnason, Petersen, & Pálsson, 1998). In contrast, microsatellite studies suggest range‐wide isolation by distance (O'Leary, Coughlan, Dillane, McCarthy, & Cross, 2007), and significant structure in waters off North America (e.g., Flemish cap, Bentzen, Taggart, Ruzzante, & Cook, 1996; inshore vs. offshore, Ruzzante, Taggart, Cook, & Goddard, 1996; Arctic populations, Hardie, Gillett, & Hutchings, 2006), Norway (Knutsen, Jorde, André, & Stenseth, 2003), and the North Sea (Hutchinson, Carvalho, & Rogers, 2001). Furthermore, genome scans of nuclear SNP markers have suggested the presence of local adaptation and temperature gradients at both large and small scales (Árnason & Halldórsdóttir, 2015; Berg et al., 2016; Bradbury et al., 2010, 2013; Nielsen et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such stable but high gene flow population structures were found in Atlantic herring in Swedish waters (F ST = 0.002-0.003, Larsson et al 2010) Jørgensen et al 2005). Temporally stable and significantly differentiated structures with high gene flow were also found in major Atlantic cod (Gadus morhua) populations (F ST = 0.0012-0.0400, Poulsen et al 2006) even over small geographic scales (F ST = 0.0023, Knutsen et al 2003) as reviewed by Hauser and Calvalho (2008). Chemical marking of otoliths previously revealed that 53-70% of herring that migrate to Miyako Bay for spawning were hatcheryreared progeny of wild herring that migrated to Miyako Bay and were released at a TL of 5 cm in Miyako Bay .…”
Section: Discussionmentioning
confidence: 88%